Comparative analysis of C9orf72 and sporadic disease in an ALS clinic population. (6th September 2016) - Umoh, Mfon E.; Fournier, Christina; Li, Yingjie; Polak, Meraida; Shaw, Latoya; Landers, John E.; Hu, William; Gearing, Marla; Glass, Jonathan D.
Abstract : Objective: We investigated whether the C9orf72 expansion mutation in patients with amyotrophic lateral sclerosis (ALS) is associated with unique demographic and clinical features. Methods: Between 2001 and 2015, approximately half of all patients attending the Emory ALS Clinic agreed to donate DNA for research. This research cohort of 781 patients was screened for the C9orf72 expansion, and demographic and clinical data were compared between those with and without the C9orf72 mutation. For mutation carriers without a family history of ALS, we sought further family history of dementia and other non-ALS neurodegenerative diseases in first-degree relatives. Results: The C9orf72 expansion was identified in 61 patients (7.8%). Compared to those without the expansion mutation, these patients did not differ in race, age, or site of onset. As expected, C9orf72 patients were more likely to have a family history of ALS (59% vs 7.9%) and to present with comorbid frontotemporal dementia (FTD) (14.8% vs 1.7%). Survival was shorter in patients with the expansion (log-rank χ 2 [1] = 45.323, p < 0.001). Further investigation in 28 patients initially categorized as having no known family history of ALS identified a family history of dementia in 16 cases; 6 of these had characteristics suggestive of FTD. Conclusions: Comparing the C9orf72 ALS population to the general ALS population, there were no differences in race, age at onset, or proportion of patients with bulbar onset disease. Differences identified in patients with the C9orf72 mutation included shortened survival and an equal proportion of men and women. In addition, we found that assessing family history for dementia may identify other family members likely to be carrying the C9orf72 expansion, reduce the number of sporadic cases, and thus increase our understanding of disease penetrance.